2017
DOI: 10.1128/jcm.02338-16
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 11 Phenotypic Assays for Accurate Detection of Carbapenemase-Producing Enterobacteriaceae

Abstract: Early identification of carbapenemase-producing Enterobacteriaceae (CPE) is essential to prevent their dissemination within health care settings. Our objective was to evaluate the accuracy of 11 phenotypic assays for the detection of CPE. Two collections of carbapenem-resistant Enterobacteriaceae (CRE) isolates were evaluated, including 191 retrospective isolates (122 CP-CRE and 69 non-CP isolates) as well as 45 prospective clinical isolates (15 CP-CRE and 30 non-CP-CRE) obtained over a 3-month period. The sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
102
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(114 citation statements)
references
References 19 publications
10
102
1
1
Order By: Relevance
“…To the best of our knowledge, this is the most comprehensive evaluation of phenotypic assays for CPNF identification. The sensitivity of carbapenemase detection for P. aeruginosa was 93 to 100% for most assays and was comparable to the accuracy of these assays for CPE detection (4). In contrast, all tests had compromised sensitivity when used to identify carbapenemase-producing A. baumannii.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…To the best of our knowledge, this is the most comprehensive evaluation of phenotypic assays for CPNF identification. The sensitivity of carbapenemase detection for P. aeruginosa was 93 to 100% for most assays and was comparable to the accuracy of these assays for CPE detection (4). In contrast, all tests had compromised sensitivity when used to identify carbapenemase-producing A. baumannii.…”
Section: Discussionmentioning
confidence: 76%
“…Of note, CLSI is reevaluating their endorsement of the Carba NP assay for detecting carbapenemase producers among carbapenem-resistant A. baumannii isolates. For more details on the relative pros and cons of the various phenotypic assays tested in this study, we refer the reader to previous work from these investigators (4). A notable limitation to this work is that there were small numbers of isolates producing any particular carbapenemase enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the original description of the assay, the authors reported 100% correlation with carbapenemase gene PCR. However, subsequent studies show reduced sensitivity of the CIM assay for the detection of both OXA-48 and NDM carbapenemases (21,22). To improve sensitivity for the detection of carbapenemases that are expressed at low levels or that naturally have weaker hydrolytic activities, the mCIM assay uses less organism (1-l versus 10-l loopful), a longer incubation period of the disk-bacterial suspension (4 h versus 2 h), and a different suspension matrix (tryptic soy broth versus water) than the original CIM assay.…”
mentioning
confidence: 99%